(untitled) (Al-Academy, 2023)
This research aims to clarify the role of Iraqi nature in the style of the artist Ayath Al-Doori. Through it, the spotlight was shed on the aesthetic of Iraqi nature, its importance and its relationship to art, and its pioneering role in the style of the Doori artist. The research included two axes: the theoretical axis and the applied axis. The first theoretical axis deals with two topics: The first topic: the aesthetic of Iraqi nature as part of the life and methods of Iraqi artists from ancient times until today, including the periodic artist. The second topic: the league artist touched on the private life of the league artist. As for the second (applied) axis, it includes the research community, the research sample models, the research tool, the research method and the analysis of the research sample models. Then this study ends with the result and then the sources.